A Reflection on the Political Rights of Minorities in Islamic Jurisprudence and Contemporary Law Texts - Alireza Ebrahimi  (پژوهش‌های فقهی مسائل مستحدثه, 2023)
Received: 2023 Jun 27  |   Recieved in revised form: 2023 Aug 9   |   Accepted: 2023 Aug 23   |   Published: 2023 Oct 23The protection of political rights of minorities is a significant concern within the realm of Private International Law. Islamic countries, which operate under an Islamic legal system, have their own set of rules, judgments, and conditions that apply to all matters, including the treatment of minorities. The research aims to examine how different types of minorities, as defined in Shīa jurisprudence texts and private international law, are afforded political rights, specifically in the Islamic Republic of Iran. In international law, minorities encompass religious, racial, and ethnic groups, whereas in Islamic law, minorities exclusively refer to religious minorities. This is because race and ethnicity cannot form the basis for differentiation in rights and obligations among citizens. The research explores the relationship between the general and specific aspects of Islamic and private international law texts, while also analyzing various aspects of Arba’e (the four major schools of Shia jurisprudence). Crucial issues addressed include the permissibility or impermissibility of religious minorities, such as Zoroastrians, Christians, and Jewish, to serve as lawyers, judges, and witnesses. The study also investigates unknown minorities. With reference to the Holy Quran, particularly the verse prohibiting alliances with disbelievers (nafye sabīl), it is argued that entrusting grave matters of legal decisions like judging to non-Muslims is not allowable. This is an obligatory principle in Islamic international law. Furthermore, many aspects of private international law can be examined through the lens of ensuring a peaceful coexistence with non-Muslim dhimmis (protected religious minorities) and under the system of jizya (tax). The research methodology employed is inferential-analytical, and the data was collected from library resources and statistical information.Ebrahimi, A.R. (2023) A Reflection on the Political Rights of Minorities in Islamic Jurisprudence and Contemporary Law Texts. Quarterly of New Perspectives in Islamic Jurisprudence, 1 (1) 142-162. Doi: https://doi.org/10.22091/RCJL.2023.9096.1016 .